The brachyceran de novo gene PIP82, a phosphorylation target of aPKC, is essential for proper formation and maintenance of the rhabdomeric photoreceptor apical domain in Drosophila - Zelhof, Andrew C. (PLoS Genet, 2020)
The Drosophila apical photoreceptor membrane is defined by the presence of two distinct morphological regions, the microvilli-based rhabdomere and the stalk membrane. The subdivision of the apical membrane contributes to the geometrical positioning and the stereotypical morphology of the rhabdomeres in compound eyes with open rhabdoms and neural superposition. Here we describe the characterization of the photoreceptor specific protein PIP82. We found that PIP82’s subcellular localization demarcates the rhabdomeric portion of the apical membrane. We further demonstrate that PIP82 is a phosphorylation target of aPKC. PIP82 localization is modulated by phosphorylation, and in vivo, the loss of the aPKC/Crumbs complex results in an expansion of the PIP82 localization domain. The absence of PIP82 in photoreceptors leads to misshapped rhabdomeres as a result of misdirected cellular trafficking of rhabdomere proteins. Comparative analyses reveal that PIP82 originated de novo in the lineage leading to brachyceran Diptera, which is also characterized by the transition from fused to open rhabdoms. Taken together, these findings define a novel factor that delineates and maintains a specific apical membrane domain, and offers new insights into the functional organization and evolutionary history of the Drosophila retina.